A study on fattening Ethiopian sheep. II. Performance of Adal lambs on supplemented grazing - Galal, E.S.E.; Tesfazgy, A.; Awgichew, K. (1979)
The study included two trials, each of two phases, to investigate the feasibility of finishing Adal lambs on irrigated pasture and the effect of concentrate supplementation. Fifty-one ram lambs with initial mean weight of 11.9 kg and mean age of 18 week were used in phase 1 Trail 1 while phase 2 of the same trail had 50 of the lambs used in phase 1 with an average initial weight of 18.3 kg and a mean initial age of 41 weeks. Phase 1 lasted for 18 weeks while phase 2 lasted for 10 weeks. In phase 1, a concentrate supplement of 300 g/head/day increased average daily gain (p